2019
DOI: 10.1021/acsanm.9b01436
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Spectroscopy Characterization of Breast Cell Phenotypes: Effect of Nanoparticle Geometry

Abstract: The use of surface-enhanced Raman spectroscopy (SERS) to delineate between the breast epithelial cell lines MCF10A, SK-BR-3, and MDA-MB-231 is explored utilizing varied morphologies of gold nanoparticles. The nanoparticles studied had spherical, star-like, and quasi-fractal (nanocaltrop) morphologies and possessed varying degrees of surface inhomogeneity and complexity. The efficacy of Raman enhancement of these nanoparticles was a function of their size, their surface morphology, and the associated density of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…The Raman shift peak frequencies that we followed and analyzed correspond to those characteristic of aromatic amino acids at 657, 816, 837, 845, 965, 1006, 1012 and 1131 cm –1 29 , 54 58 , and to S–S bonds at 503 cm −1 29 . The assignment of the vibrational modes of these peaks is shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The Raman shift peak frequencies that we followed and analyzed correspond to those characteristic of aromatic amino acids at 657, 816, 837, 845, 965, 1006, 1012 and 1131 cm –1 29 , 54 58 , and to S–S bonds at 503 cm −1 29 . The assignment of the vibrational modes of these peaks is shown in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…For example, a comparison between the non-malignant MCF-10A with malignant SK-BR-3 breast cell lines indicates an increase in the concentration of tyrosine-rich proteins, as evidenced by the high intensity band at 837 cm −1 , in accordance with the structure of the HER-2 receptor 29,[59][60][61][62] . In addition, it has been observed that the Raman spectra corresponding to aromatic amino acids in malignant SK-BR-3 and MDA-MB-231 breast cell lines exhibit intense bands characteristic to tyrosine, phenylalanine, and tryptophan, suggesting the enhancement in the expression of such aromatic amino acid rich proteins in malignant cells 29,[63][64][65][66][67][68] . This phenomenon is not restricted to breast cancer alone, but is prevalent in other malignancies such as pancreatic cancer, colon cancer, gastric cancer, and lung cancer.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations